1998
DOI: 10.1007/s004240050686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dehydration and rehydration on body temperatures in the black Bedouin goat

Abstract: The temperatures of the arterial blood and the brain in black Bedouin goats were measured continuously by miniature data loggers. The animals were either euhydrated or dehydrated to 75-80% of the initial body mass by withholding water for 3-4 days during exposure to intense solar radiation. The daily blood temperature means and maxima of were significantly higher in dehydration than in euhydration, but 40 degreesC was rarely exceeded even during the hot hours of the day. Selective brain cooling occurred in euh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
(48 reference statements)
4
49
2
Order By: Relevance
“…Thus, the reduction in heart rate in the water-restricted goats suggests that they reduced their metabolism in order to conserve water and to compensate for the reduction in feed intake. The RR, even in treatment 1, was much lower than those induced under combination of dehydration and heat stress (Baker, 1989;Jessen et al, 1998), indicating that the goats in the present experiment were still far from situations that necessitate induction of heavy panting to maintain thermoregulation (Silanikove, 2000a).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, the reduction in heart rate in the water-restricted goats suggests that they reduced their metabolism in order to conserve water and to compensate for the reduction in feed intake. The RR, even in treatment 1, was much lower than those induced under combination of dehydration and heat stress (Baker, 1989;Jessen et al, 1998), indicating that the goats in the present experiment were still far from situations that necessitate induction of heavy panting to maintain thermoregulation (Silanikove, 2000a).…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, the increase in deep (rectal) temperature and udder skin temperature were quite modest in comparison with the responses of animals that were exposed to severe heat stress (Silanikove, 2000a), indicating that the heat stress under the present conditions did not induce significant challenge on the thermoregulation capacity of the goats. For comparison, under dehydration, the mean daily maxima of deep temperature was 0.5°C to 0.9°C higher in dehydrated goats than in hydrated ones, which was a result of a reduction in evaporative heat loss (Baker, 1989;Jessen et al, 1998). Thus, only in treatment 1, in which the restriction level was 90% of control, the prevailing heat stress induced an increase in deep body temperature that resembled a modest response under combined effects of heat stress and dehydration.…”
Section: Discussionmentioning
confidence: 98%
“…Jessen et al (1998) offered water in different temperatures for Bedouin goats and reported that body temperature changed according to the temperature of the water, but this effect was observed only for a few seconds. The most likely explanation for the variation of rectal temperature is the nychthemeral variation (Kleiber 1975).…”
Section: Resultsmentioning
confidence: 99%
“…Also, we deprived the goats of drinking water in March, as could occur in summer seasons they might encounter, but not in winter. Water deprivation increases abdominal temperature in heat-stressed goats (Nijland and Baker, 1992;Jessen et al, 1998), but there is no evidence that short-term water deprivation compromises thermoregulation in animals not exposed to heat stress (Baker and Doris, 1982;Fuller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%